Main Capabilities and Features of Ultra Wideband (UWB) Radars - Immoreev, I.J. (Радиофизика и радиоастрономия, 2002)
This review paper discusses the differences between ultra wideband (UWB) radars and the conventional narrow-band radars. The features are shown of the generation, radiation and processing of UWB radar signals evoked by the change of the signal waveform in the process of location, by appearance of the mutual dependence between the signal waveform and antenna directivity, and other. The possibility for the reception of the target radioimage is shown.